Edukasi Penanganan Gizi Balita pada Kondisi Kedaruratan Bencana Kebakaran di Wilayah Kerja Puskesmas Maccini Sawah - Nurbaiti Nurbaiti; Sanghati Sanghati; Nurhayati Nurhayati; Basmalah Harun; Nijar Wijayanti; Rista Abubakar (Jurnal DIKMAS, 2021)
Disasters are events either natural or non-natural that cannot be predicted in advance. The impact of natural disasters can be in the form of comprehensive environmental damage that can cause mass human deaths. Fires can occur anywhere and at any time, fire management needs to be understood so that when a fire occurs there are no casualties. Thus, preparedness is needed to face disasters. Indonesia is one of the disaster-prone countries. The age groups that are vulnerable to this problem are babies and toddlers. Disaster management specifically for this age group includes the Infant and Child Feeding (IYCF) program. The aim of this service is to meet the nutritional needs of the infant and toddler age group in the Maccini Sawah Community Health Center Working Area, so that it can prevent nutritional problems due to disasters and can handle nutritional problems. The method used in service activities is demonstrating IYCF to the community and also providing IYCF counseling at disaster sites. The results achieved were that IYCF education ran smoothly so that feeding services for the infant and toddler groups were carried out well in phase one of the emergency. IYCF is mandatory in disaster situations to prevent and treat acute nutritional problems during disasters